MONITORING OF MICROBIOLOGY QUALITY RAW WATER AND REFILLED DRINKING WATER DURING COVID-19 - Herniwanti Herniwanti; Endang Purnawati Rahayu (The Indonesian Journal of Public Health, 2022)
Introduction: Riau province regency / city data for drinking water depots in 2020 show that the largest number of Pekanbaru City in Riau Province has refill drinking water depots, there are 440 depots consisting of 220 feasible depots while 227 depots are not feasible. This research was conducted in the Tampan sub-district which is the most densely populated city of Pekanbaru. The purpose of this study was to evaluate the microbiological quality standards (Coliform) for refill drinking water depot, raw water source quality standards and population well quality standards during Covid-19. Methods: This research is quantitative descriptive analytic with triangulation methods observation with laboratory tests, in-depth interviews with correspondents of depot officers and residents of drinking water wells. The test was carried out at the UPT health and environment laboratory of the Riau provincial health office. Result: Data analysis  compared 7 samples with laboratory test results according to quality standards. The results of the analysis stated that there were no Coliform bacteria in the tested samples. The source of raw water from housing will have better standard of quality the deeper it is. Conclusion: There is no periodic supervision from the health office / Puskesmas to drinking water depot during the Covid-19 period which is usually routinely carried out every 3-6 months according to regulation of ministers of health no.736,2010 concerning supervision of drinking water quality. Housing developers are required to provide a clean water source from a proper borehole from the start of housing development.